Skin manifestations of hematologic malignancies (Bangladesh Medical Journal, 2016)
Hematologic malignancies can present with various cutaneous manifestations. These include specific cutaneous diseases & non-specific cutaneous lesions. Non-specific skin lesions are more common in patients with hodgkins diseases. Generalized severe pruritus may precede other findings of Hodgkins disease by many months . So an evaluation for underlying lymphoma should be considered in patient with severe itching. Leukemia cutis (specific skin lesions of Leukemia) most commonly occurs concomitant with or following the diagnosis of leukemia. The skin may also be the site of relapse of leukemia after chemotherapy. Uncommonly leukemia cutis may be identified while the bone marrow & peripheral blood are normal. Those patients are classified as aleukemic leukemia cutis. This cross sectional observational study was carried out in the Hematology department of Bangabandhu Sheikh Mujib Medical University from January 2012 to January 2013 with the intention to know the prevalence of skin manifestations of hematologic malignancies & to help diagnose and manage hematologic malignancies in some extent. Total 127 consecutive patients who were already diagnosed as haematological malignancies & hospitalized were evaluated at the period of one year. Different types of cutaneous lesions were found in our study population, Infections were the highest number, 32(25.19%) patients suffering from various infections. Other findings includemalignant infiltration, 10(7.87%); hemorrhagic 121 lesions (petechia and ecchymosis), 17(13.38%); drug reaction, 5(3.93%); gingival hyperplasia, 3(2.36%); pruritus, 23(18.11%); pigmentation, 20(15.74%); prurigo, 8(6.29%) and ichthyosiform lesion, 19(14.96%).Bangladesh Med J. 2014 Sep; 43 (3): 121-124